(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Payment Instruments are a group of most prominent and promoted digital applications for mobile. These instruments have been instrumental in conducting a digital transaction, thereby helping the seller to facilitate a sales process. For many cash might still be undisputable if proper methods, processes and procedure are not adopted and updated time to time. From proper education, awareness to being courteous to users thereby encouraging the use of digital means to complete a transaction is still felt necessary. Cash along with digital platforms, can shape the future of payment processing. Therefore, there is a need to facilitate the use of Online Payment Instruments including Prepaid Payment Instruments and UPI applications. To be specific, an e-Wallet carries most of the financial services that is built into it, which is encouraging. Electronic Payment Instruments including plastic cards, e-Wallets, UPI apps etc. have always been a fast to use digital platform for digital transactions. Therefore, the present study will focus on important payment platforms being actively used by sellers and study their perception of these services including willing customers. Moreover, the study makes an attempt to find the significance of one platform over the other. Hence, the authors have highlighted the significance of various payment platforms including Cash, e-Wallets, Plastic Cards and Other available means in the City of Dibrugarh (India). These services are used by shopkeepers, restaurants and businesses when they enter into a sale process with customers.